Primary central nervous system Hodgkin Lymphoma: A case discussion and a hypothesis on the etiology - Alfaseh, Ahmad; Rajeh, Mhd Nabeel; Hamed, Ghiath (Avicenna Journal of Medicine, 2019)
Hodgkin Lymphoma (HL) is a systemic disease with involvement of the cervical, supraclavicular, and mediastinal lymph nodes. It is commonly diagnosed in patients within the second and third decades of their lives. Diagnosis is usually made based on the distinct morphological and immunohistochemical characteristics, with the tissue biopsy being the cornerstone of workup. Extranodal presentation of HL is unusual and seldom encountered. Primary HL of the central nervous system (CNS) is exceedingly rare. We herein report a case of a 38yearold male patient who was diagnosed with primary CNSHL. The patient was treated with complete surgical resection followed by radiotherapy and chemotherapy. The patient was diseasefree for 7 years postoperatively without any clinical evidence of relapse. We also discussed a possible role of CNS regulatory Tcells (Tregs) in developmental primary CNSHL.
Keywords: Central nervous system lymphoma; cerebellar tumor; Hodgkin Lymphoma; T-regulatory cells